Prevalence of mesiodens among six- to seventeen-year-old school going children of Indore - V Khandelwal; A U Nayak; R B Naveen; N Ninawe; P A Nayak; S V Sai Prasad (Wolters Kluwer Medknow Publications, 2011)
Introduction: 'Mesiodens' are the supernumerary teeth present in the midline of the maxilla between the two central incisors. These mesiodens are the most common supernumerary teeth and are usually responsible for eruption disturbance or delay of the maxillary anterior permanent teeth. The present study seeks to investigate the prevalence of mesiodens among school going children in Indore City, India. Materials and Methods: The study was a retrospective collection of data to evaluate the prevalence of mesiodens among 3896 children, whose ages ranged between six and seventeen years. Results: The results showed that males were affected approximately 1.2 times as frequently as females; 3.18% of the total screened population had mesiodens and among the affected population 4.03% had two or more mesiodens. Most of the mesiodens were conical in shape. The age, sex distribution, number of mesiodens per patient, shape, and direction of the eruption are presented in this study. Conclusions: The present study gives an insight into the prevalence of mesiodens among school going children of Indore city. A coincidental finding in our study has been the high risk of trauma associated with the occurence of mesiodens. This finding makes it mandatory to include mesiodens as a risk factor in traumatic dental injuries. Early diagnosis and management of these otherwise considered mild factors must be made mandatory in pediatric dentistry.